Shoot Production and Metabolite Content of Waterleaf with Organic Fertilizer - Ismail Saleh, Ismail Saleh; Aziz, Sandra Arifin; Andarwulan, Nuri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2014)
ABSTRACTWaterleaf shoot (Talinum triangulare (Jacq.) Willd) is consumed as vegetable that contains some metabolites. The purpose of this research was to investigate the effect of organic fertilizer on shoot production and its metabolites i.e. protein, vitamin C, flavonoid, and peroxidase enzyme (POD) activity at 10, 12, and 14 weeks after planting. This experiment was conducted at Leuwikopo Experimental Station, Bogor, Indonesia from November 2012-February 2013. The organic fertilizers applied were cow manure (CM) (12.3 ton ha-1), rock phosphate (RP) (1.5 ton ha-1), and rice-hull ash (RH) (5.5 ton ha-1). These organic fertilizers were combined into four treatments by using minus one test method and one control. Each treatment was repeated three times. The result showed that combination of organic fertilizer had the same effects on shoot production and metabolite content of waterleaf. It showed that the amount of organic fertilizers was not significantly sufficient to contribute nutrients to the plant. Keywords: flavonoid, POD activity, repeated harvesting, Talinum triangulare, vitamin C